Gender differentials in educational attainment in rural Nigeria (2022)
Education, identified as the substratum of any serious nation’s growth and development, is regarded as an instrument for social change, as well as the process of preparing an individual to become a functional and acceptable member of society. It also ensures the character and moral development of the young learners and the development of sound attitudes for both genders. This study examined gender differentials in educational attainment in rural Nigeria, employing the t-test, analysis of variance and the ordinary least squares regression model for analysis. The main factor which had negative effects on educational attainment of female-headed households was the cost of schooling while factors such as the organization running the school and means of transportation had positive effects on the educational attainment of female households. On the other hand, while age and occupation of the household head had negative effects on male educational attainment, factors such as the value of asset, the organization running the school and means of transportation had positive effects. The approval and implementation of necessary legislation and policies on education targeted at rural dwellers is of utmost importance. This could center on the provision of more nearby government-owned schools as well as awareness creation on the essence of educating both genders, especially the girl child, with a focus of achieving gender balance in educational attainment.